2010
DOI: 10.1016/j.ijpsycho.2010.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Group independent component analysis of resting state EEG in large normative samples

Abstract: EEG (Electroencephalography) resting state was studied by means of group blind source separation (gBSS), employing a test-retest strategy in two large-sample normative databases (N=57 and N=84). Using a BSS method in the complex Fourier domain and a model-driven distributed inverse solution we closely replicate both the spatial distribution and spectral pattern of seven source components. Norms were then constructed for their spectral power so as to allow testing patients against the norms. As compared to exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 118 publications
4
64
1
Order By: Relevance
“…Using recordings obtained at rest in 144 subjects, Congedo et al [80] reported seven sources distributed across the cortex, where three of them were also related to the Precuneus, that would serve to assessment and diagnosis of abnormal brain functioning. In our case, gICA helps to link differences between asymptomatic subjects at scalp level [22] and brain cortex, showing a region that can be reliably measured using inverse solution methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using recordings obtained at rest in 144 subjects, Congedo et al [80] reported seven sources distributed across the cortex, where three of them were also related to the Precuneus, that would serve to assessment and diagnosis of abnormal brain functioning. In our case, gICA helps to link differences between asymptomatic subjects at scalp level [22] and brain cortex, showing a region that can be reliably measured using inverse solution methods.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the approach given by Congedo et al [80] we obtained the spatial filters using young asymptomatic subjects. The differences between groups using the spatial filters obtained by gICA were validated by the positive results comparing SCr and Ctrl-2, which were not included in the gICA analysis, and were also confirmed by the wMNE results, that in our case served also as cross-validation results.…”
Section: Discussionmentioning
confidence: 99%
“…BSS techniques combined with source localization provide a useful tool for exploring task-related EEG (eg. Delorme et al, 2007b), as well as applications in realtime EEG fields such as neurofeedback and brain-computer interfaces (Congedo, 2006) and clinical studies comparing patients to normative databases (Congedo et al, 2010).…”
Section: Source Localization With Ajdc and Sloretamentioning
confidence: 99%
“…More recently, the AJDC method has been extended to group data analysis to obtain a common set of filters describing the sample under study (Congedo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the independent component NFB is based on the group EEG ICA of normal subjects that revealed 7 independent sources replicated in 2 normative databases [13]. The component of interest for this study is component number 1 as described in the study by Congedo et al [13] because it has been reported to differentiate between OCD patients and healthy controls [14].…”
Section: Introductionmentioning
confidence: 99%